The larva of Neoneura ethela Williamson, 1917 (Odonata: Protoneuridae) - de Souza, Luiz Onofre Irineu; Pepinelli, Mateus; Neiss, Ulisses Gaspar (Zootaxa, 2012)
The last-instar larva of Neoneura ethela Williamson is described and illustrated based on one larva collected from a thermal water river in Brazil, State of Goiás and reared in the laboratory. The larva of N. ethela can be distinguished from all other South America Neoneura larvae by the following combination of characters: one pair of premental setae, S8–10 with a row of short spines along distal border, lateral gills a little longer than length of abdomen, ventral border of lateral gill armed with a row of about 24 spines. We provide a key to the species of known South American larvae of Neoneura.